Ways to increase national economic potential - Sodikov Zokir Rustamovich (Zien Journals, 2024)
The article analyzes the possibilities of national economic development and the importance of introducing digital technology in it. It is also based on the achievements of increasing national economic potential, modernization of production and diversification of foreign trade
Keywords: national economy; production; modernization; diversification